Robert C.H. Sweeny’s Why Did We Choose to Industrialize?: Montreal, 1819–1849: A Round Table Commentary - FAHRNI, MAGDA (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2017)
Readers of Robert C.H. Sweeny’s Why Did We Choose to Industrialize? Montreal, 1819–1849 will find old questions, interrogated with classic quantitative methods, and new questions, methods, and ways of writing history. This book is of interest for those historians who wish to understand the debate around the process of industrialization, or the impact of the arrival or industrial capitalism on a city. What is more, Sweeny’s book constitutes proof that the craft of history is an exercise in life-long learning, allowing the reader to find something new in each reading.